Design and evaluation of a power tiller vegetable seedling transplanter with dibbler and furrow type - Md Sumon Miah; Md Mashiur Rahman; Muhammad Arshadul Hoque; Sobhy M. Ibrahim; Muhammad Sultan; Redmond R. Shamshiri; Mustafa Ucgul; Mahedi Hasan; Tasneem Nahar Barna (Heliyon, 2023)
Vegetable production plays a vital role in ensuring food security in Bangladesh. However, the majority of vegetable seedlings are currently transplanted manually, which is not only time-consuming but also labor-intensive and costly. In this context, a semi-automated transplanter can be considered as an alternative solution for mechanized seedling transplanting. To mechanize seedling operations, two types of transplanters were designed, fabricated and tested: the power tiller-operated semi-automatic dibbler vegetable seedling (DVS) transplanter and the furrow opener vegetable seedling (FVS) transplanter. The goal was to evaluate their performance and impact on field crop productivity. In the DVS transplanter design, the larger sprocket was adjusted to enhance the precision of hole-making by pressing the dibbler into the soil, creating holes where seedlings would be transplanted. On the other hand, the FVS transplanter utilized a furrow opener to create furrows, and the seedling is placed in these furrow at a specific distance from the furrow opener wall, where the distance between seedlings within the furrow could be adjusted based on the specific requirements of the seedling crop. The results of the evaluation indicated that both transplanters successfully planted seedlings without any missing placements, while hole covering was achieved at 115 and 118.2% for the DVS and FVS transplanters, respectively. The field capacity and field efficiency for both transplanters were determined to be 0.05 ha h−1 and 61.18%, respectively, with a coefficient of variation of 5% or less. Field tests conducted with brinjal crops at a forward speed of 1.2 km h−1 and a spacing of 0.7 × 0.6 m demonstrated that both designs yielded higher yield productivity compared to manual transplantation. Additionally, no issues related to vegetative development were observed. Both transplanters exhibited promising performance and significant potential in terms of accurately transplanting seedlings, and ensuring satisfactory transplantation quality. Furthermore, these transplanters offer several advantages, including less time-consuming, lower labor demands and even distribution of seedlings. This design encourages small to medium-level farmers seeking to engage in mechanized vegetable farming practices.